2023
DOI: 10.1039/d2su00079b
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised graphite felt anodes for enhanced power generation in membrane-less soil microbial fuel cells

Abstract: There is a global need for sustainable and clean technologies that can actively contribute to reach the net-zero carbon goal by 2050. Soil microbial fuel cell (SMFC) technology has a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…It was found that graphite foam produced enhanced power density and cell biomass compared with the other types of anode materials [ 28 ]. Table S1 presents the cost of different 2D and 3D carbonaceous anode materials for MFCs [ 29 ].…”
Section: Architectural Design For Mfc Constructionmentioning
confidence: 99%
“…It was found that graphite foam produced enhanced power density and cell biomass compared with the other types of anode materials [ 28 ]. Table S1 presents the cost of different 2D and 3D carbonaceous anode materials for MFCs [ 29 ].…”
Section: Architectural Design For Mfc Constructionmentioning
confidence: 99%
“…Aerobic and anaerobic soil microbial fuel cells (SMFCs) have been constructed with single and multiple chambers, optimizing electricity generation and microbial activity. For instance, different types of graphite felt electrodes have been tested as the anode in an air-cathode and membrane-less SMFC [9]. Researchers combined a composite anode material with a conductive polymer and a transition metal oxide to enhance biofilm formation and electrogenesis.…”
Section: Introductionmentioning
confidence: 99%